Company’s internal characteristics, environmental uncertainty, the use of accounting information, and the performance of SMEs - Lodovicus Lasdi; Teodora Winda Mulia (Journal of Economics, Business, and Accountancy Ventura, 2014)
Accounting information allows management to implement strategies and operational activities which are necessary to achieve the objectives of the organization as a whole, including on Small and Medium Enterprises (SMEs). Many SMEs have difficulty in understanding the accounting information well, whereas the accounting information plays an important role in creating the flow of financial information to support sur- vival or going concern of the SMEs. This study has two objectives. First, to determine the effect of knowledge of accounting, business scale, business experience, and types of businesses on the use of accounting information with the environmental uncertainty as a moderating variable on SMEs in Surabaya and Sidoarjo, second, to determine the effect of the use of accounting information on the performance of SMEs. The result shows that knowledge of accounting, business scale, and business experience affect the use of accounting information. However, the variable of type of business does not affect the use of accounting information. The result of hierarchical regression analysis shows that the variable of environmental uncertainty strengthens the efffect of the variables of knowledge of accounting, business experience, and type of business on the use of accounting information. However, the environmental uncertainty does not strengthen the effect of business scale on the use of accounting information. The test result also shows that the use of accounting information can improve the performance of SMEs.